Maitland en la atención fisioterapéutica del adulto con pinzamiento subacromial. Cuerpo de Ingenieros del Ejército. Quito, 2019. - Paul Alejandro, Carrera Quimbita (2019)
This project corresponds to Maitland physiotherapy care in the adult Subacromial Pinching in the Corps of the Army in Quito, 2019 whose objective was to determine Maitland benefits for patients diagnosed with subacromial impingement syndrome. The tore where Maitland was applied to 35 adult patient diagnosed with the disease mentioned the type of project is documentary, the data were based on physiotherapy clinic records, and the level of research is descriptive to know the characteristic of the conditions because the application posterior to an initial evaluation applied Maitland in patients who were diagnosed, cross section. The descriptive statistical method was used for this testing Neer, Hawkins Kennedy, and numeric rating scale that were fundamental for better diagnostic for pathology results the generates the Exel software.